The Triad of Divine “Moments” in the Latin Work of Meister Eckhart - Castello, Sofía (Anales del Seminario de Historia de la Filosofía, 2021)
In this article we intend to present a hermeneutical proposal for the study of the Latin work of Meister Eckhart. Thus, we consider that three “moments” can be identified within God “superabundant”, “in all his expression” –which represents reality as such: God in “his first aspect”, as cause; God in “his second aspect”, as effect; and God in “his third aspect”, as creature. The exposition of these “moments” tends to express the movement of identity and difference that it is constitutive of the Divinity, hence allowing it being everything, and nothing of everything. This line of interpretation points out clearly the Neoplatonic inheritance of Eckhart.